Cytotoxic Activity of Selected Nigerian Medicinal Plants. Issue 2 (2nd April 2020) - Aladesanmi, Adetunji Joseph; Famuyiwa, Funmilayo Gladys; Oriola, Ayodeji Oluwabunmi; Oguntimehin, Samuel Ayoolu; Aiyedun, Priscilla Oluwakemi; Arthur, Gilbert
ABSTRACT: The study investigated eight Nigerian medicinal plants: Artocarpus communis fruit (Ac-F), Cassia sieberiana root bark (Cs-R), Eugenia uniflora leaf (Eu-L), Hibiscus rosa-sinensis flower (Hr-F), Laportea aestuans aerial part (La-A), Massularia acuminata stem bark (Ma-S), Trichilia heudelotii leaf (Th-L), and Xylopia aethiopica fruit (Xa-F), for anticancer activity. The alcoholic extracts of the plants were tested against human prostate DU-145, breast JIMT-1, and pancreatic BxPC-3 cancer cell lines using Methanethiosulfonate (MTS) assay, where chlorambucil was used as positive control. The active fractions were solvent-partitioned and tested against the three cancer cell lines. The results showed a concentration dependent decrease in cancer cell viability and cytotoxicity of four of the extracts, namely Massularia acuminata stem bark (Ma-S), Xylopia aethioipica fruit (Xa-F), Laportea aestuans aerial part (La-A), and Eugenia uniflora leaf (Eu-L). The petroleum ether fraction of X. aethiopica fruit (XP) demonstrated the greatest anticancer activity. At 75 µg mL −1, XP (37.2 ± 4.4%) was comparable to chlorambucil (39.88 ± 2.41%), in its cytotoxicity against breast cancer cell line JIMT-1.